2002
DOI: 10.1021/ja027276m
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Ring Size of a Cyclic Nonribosomal Peptide Antibiotic by In-Frame Module Deletion in the Biosynthetic Genes

Abstract: Many natural products of therapeutical and biotechnological importance are nonribosomally synthesized peptides. Structural hallmarks of this class of compounds are the occurrence of unusual amino acids, mostly cyclic peptide backbones, and numerous further modifications such as acylation, heterocyclic ring formation, and glycosylation. Because of their structural complexity, chemical synthesis is usually an unattractive route to these molecules. In contrast, genetic engineering of the biosynthesis genes emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 15 publications
1
60
0
3
Order By: Relevance
“…The stepwise aminoto-carboxy-terminal elongation of the thioesterified intermediates is catalyzed by the condensation domain (C domain). These domains form the three core domains of every elongation module (33). LipNrps consists of only one module with these three core domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The stepwise aminoto-carboxy-terminal elongation of the thioesterified intermediates is catalyzed by the condensation domain (C domain). These domains form the three core domains of every elongation module (33). LipNrps consists of only one module with these three core domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the artificial engineering of NRPS assembly lines is an attractive route to prepare analogs of complex natural products (32,40). The practicability of this general concept has been demonstrated in various examples, ranging from targeted modifications of existing products to the constitution of entirely artificial NRPSs from scratch (9,24,29,31,38,44,51). For example, an artificial NRPS that catalyzes formation of the dipeptide precursor of the high-intensity sweetener aspartame was constructed de novo (10).…”
Section: Discussionmentioning
confidence: 99%
“…5a) resulted in the generation of novel surfactin derivatives substituted at the 7th position (Fig. 5b), albeit with lower catalytic efficiency and product yield (0.1-0.5% [Mootz et al, 2002]. The surfactin derivatives lysed erythrocytes, although with a reduced activity compared to the wild type peptide.…”
Section: Domain and Module Swapsmentioning
confidence: 99%
“…Mootz et al [2000] created trimodular systems that exhibited the expected biochemical activity and produced the expected product in vitro, although not with exact specificity. In a final example of module swapping, Mootz et al [2002] again used the fusion sites identified in previous work to eliminate the second module from surfactin synthetase. The d2 surfactin synthetase produced the expected product, which was isolated in 19% yield relative to the parent Bacillus subtilis strain that produces surfactin.…”
Section: Domain and Module Swapsmentioning
confidence: 99%